IDENTIFIKASI CENDAWAN PATOGEN PADA PENYIMPANAN JAGUNG SESUAI KEARIFAN LOKAL MASYARAKATDI KABUPATEN TIMOR TENGAH UTARADALAM PERSPEKTIF KETAHANAN PANGAN - MM.Endah Mulat Satmalawati; Aloysius Rusae (Politeknik Pertanian Negeri Kupang, 2017)
Corn samples were obtained from four storage locations according toexisting local wisdom in TTU district. Corn storage barn taken from Insana Barat (Mamsena), storage with fumigation without husks taken from Miomafo Barat (Haulasi), fumigation and with husks storage is taken from Naibenu (Bakitolas), storage of corn without husks taken from Bikomi Utara (Banain)The Microbiological analisis was conducted at the Laboratory of the Faculty of Agriculture Timor University in August until November 2016. The Result showed that the corn,during storage, was infected by pathogenic fungi such as Altenaria, sp, Fusarium, sp and even Aspergiluss, sp which could potentially excrete toxins. High water content correlates to the growth of pathogenic fungi that influence to food safetyÂ Key word: Corn, corn storage, fungi, pathogenic fungi